IMPLEMENTASI TEORI PEREKONOMIAN INDONESIA DALAM MENGHADAPI TANTANGAN GLOBALISASI DAN DIGITALISASI EKONOMI NASIONAL KONTEMPORER MODERN STRATEGIS - M. Ferdiyan; Reni Ria Armayani Hasibuan; Nanda Ardi Tama; Siti Khairani; Raihan Hidan Bugis (CV. Barokah Publsiher, 2025)
This study aims to analyze the implementation of Indonesian economic theory in addressing the challenges of globalization and the digitalization of the national economy in a contemporary and strategically modern era. The research employs a qualitative descriptive approach using a literature review method by examining books, academic journals, government policy documents, and other relevant sources. This study highlights the role of Pancasila-based economic theory as the foundation of the national economic system in responding to global economic dynamics and rapid digital transformation. The findings indicate that globalization and digitalization present both opportunities and challenges for Indonesia’s economy, particularly in terms of competitiveness, economic sovereignty, and equitable welfare distribution. Conceptually, the implementation of Indonesian economic theory emphasizes the role of the state in regulating and safeguarding national interests; however, in practice, it faces obstacles such as unequal access to digital technology, the dominance of global economic actors, and limitations in adaptive regulatory frameworks. Therefore, innovative, inclusive, and nationally value-oriented economic policy strategies are required to ensure sustainable economic development amid globalization and digital transformation.